2016
DOI: 10.5606/archrheumatol.2016.5793
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of High Intensity Laser and Epicondylitis Bandage in the Treatment of Lateral Epicondylitis

Abstract: Objectives: This study aims to investigate the effects of high-intensity laser therapy (HILT) and epicondylitis bandage treatment in patients with lateral epicondylitis (LE). Patients and methods: Sixty-five patients with unilateral LE (18 males, 47 females; mean age 46.5±8.1 years; range 30 to 61 years) with unilateral complaints were included. Patients were randomly assigned into two treatment groups. The first group (n=31) was treated with HILT for 10 sessions, while the second group (n=34) used only LE ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 18 publications
(21 reference statements)
0
33
0
Order By: Relevance
“…25,26 Finally, 19 studies (HILT: 11, +other interventions: 8) were included for qualitative and quantitative assessment. [11][12][13][15][16][17]19,[31][32][33][34][35][36][37][38][39][40][41][42] The characteristics of all studies in two groups are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…25,26 Finally, 19 studies (HILT: 11, +other interventions: 8) were included for qualitative and quantitative assessment. [11][12][13][15][16][17]19,[31][32][33][34][35][36][37][38][39][40][41][42] The characteristics of all studies in two groups are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…32 Conversely, the studies which did not supporting a positive effect of HILT (low differences in ES) most commonly did not specify the amount of introduced energy or the simultaneous consumption of non-steroid anti-inflammatory drugs, so it was not possible to make a judgment on whether the energy parameters may have contributed to a suboptimal outcome. 34,36,41 The consumption of non-steroid anti-inflammatory drugs may be a confounding factor in evaluating the effects of laser therapy, as identified in some studies 13,41 Some studies did not mention the effects of disease chronicity, despite the fact that this is a major factor in determining the amount of energy density and power output which is needed in the treatment protocol by laser therapy. 13,18,[32][33][34]36,38,41,42 It seems that adding thermal and non-thermal agents to HILT may enhance the effects of laser therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of previous studies have investigated the efficacy of HILT in LE. For example, Salli et al 31 investigated the HILT treatment efficacy with epicondylitis bandages and observed significant improvement in favor of the HILT in all of the hand grip strength, pain, disability, and quality of life parameters. Additionally, Akkurt et al 10 investigated the long-term HILT treatment effects and reported significant improvements in the VAS (in both activity and rest), DASH, hand grip strength, and SF-36 scores starting at the second week after treatment, which continued to increase through the sixth month.…”
Section: Discussionmentioning
confidence: 99%